(untitled) (Environment & Health, 2020)
The analysis of the data of the monitoring of harmful substances’ emissions in ambient air from the stationary sources over 2007-2017 has been carried out in the article. Objective: We assessed the dynamic changes in the ecological-and-hygienic condition of ambient air pollution in Rivne oblast by the monitoring observation data. Materials and methods: We used the laboratory data by the sanitary-and-chemical and radiological indicators of the statistical form F.18 "Report of environmental factors affecting the health status of the population" in the regions of the oblast over 2007-2017, the materials of the Main Department of Statistics in Rivne oblast, and the report on the environmental state in Rivne oblast. We systematized, processed, and analyzed research materials with the help of the descriptive, dynamic, and comparative methods. Results and discussion: During the study period, emissions of the harmful substances into the ambient air from the stationary sources in Rivne oblast decreased by 93.5%. The above is associated with a decline in the industrial production. A tendency of a decrease of the percentage of carbon monoxide from 28.3% in 2007 to 16.4% in 2017 (by 11.9%) and a tendency of an increase of the percentage of nitric oxide from 18.8% to 29.2% (by 10.4%) in the total amount of the emissions in 4 main pollutants (dust + sulfur dioxide + nitrogen dioxide + carbon monoxide) were determined. Conclusion: There is no proper state monitoring system for the condition of ambient air pollution in the settlements as a result of the liquidation of the state sanitary-and-epidemiological service.